Veterinarians and Humane Endings: When Is It the Right Time to Euthanize a Companion Animal? - Knesl, Oliver; Hart, Benjamin L.; Fine, Aubrey H.; Cooper, Leslie; Patterson-Kane, Emily; Houlihan, Kendall Elizabeth; Anthony, Raymond (Frontiers in Veterinary Science, 2017)
Current advances in technologies and treatments provide pet owners and veterinarians with more options for prolonging the life of beloved pets, but can simultaneously lead to ethical dilemmas relating to what is best for both animal and owner. Key tools for improving end-of-life outcomes include (1) sufficient training to understand the valid ethical approaches to determining when euthanasia is appropriate, (2) regular training in client communication skills, and (3) a standard end-of-life protocol that includes the use of quality of life assessment tools, euthanasia consent forms, and pet owner resources for coping with the loss of a pet. Using these tools will improve outcomes for animals and their owners and reduce the heavy burden of stress and burnout currently being experienced by the veterinary profession.